Changes in muscle composition and energy contents of golden mahseer, Torputitora (Hamilton) in relation to its spawning cycle - Basade, Yasmeen; Kapila, Suman; Kapila, Rajeev (Indian Journal of Fisheries, 2011)
Seasonal changes in the muscle compositions and energy contents of male andfemale fishes of golden mahseer, Tor putitora (Hamilton) were examined with regardto their spawning cycle during the year 1996. In pre-spawning season (April toMay), protein, fat, glycogen and energy contents tended to increase as a percentageof muscle composition, whereas, during spawning season (June to September) thesame decreased and reached a minimum in post-spawning season (October toNovember), indicating significant (p